Language Attitudes toward Varieties of EnglishAmong University Students in China - Shengnan, Li (NULL, 2023)
In an era where English serves as a lingua franca, it is essential to investigate the attitudes ofChinese English learners towards English varieties to shed light on whether non-nativeEnglish varieties should be taught in educational institutions. This study investigates Chineseuniversity students’ implicit and explicit attitudes toward British RP-accented English(BRE), General American English (GAE), Hong Kong English (HKE), and China Mandarinaccent English (CME) from a sociolinguistic perspective using Verbal-guise technique(VGT) and questionnaires. The theoretical framework of this study is based on Ryan’s(1973) model of implicit language attitudes which encompasses the dimensions of statusand solidarity, Baker’s (1992) categorization of explicit language attitudes, and Cargile etal.’s (1994) social process model of language attitudes. The objectives of this research were:1) To investigate Chinese university students’ implicit attitudes towards four varieties ofEnglish; 2) To examine Chinese university students’ explicit attitudes towards Englishlanguage and four varieties of English; 3) To compare their implicit and explicit attitudes toidentify dimensions of language attitudes that differ in the participants’ evaluativejudgements; and 4) To analyse the influence of different demographic variables on theirlanguage attitudes. Five hundred university students from four universities in Beijing,Shanghai, Guangzhou and Fuzhou, China listened to audio recordings of BRE, GAE, HKEand CME recorded by eight male and female speakers, scored them on a bipolar semanticscale. Then, they completed a questionnaire comprising 123 items that investigatedevaluative reactions towards BRE, GAE, HKE and CME speakers, attitudes toward Englishattitudes, attitudes towards four English varieties, attitudes towards learning English, andattitudes towards the use of English. The results showed that for implicit attitudes, CMEreceived the highest rating, followed by GAE, BRE, and HKE. For explicit attitudes, CME received the highest rating, followed by BRE, GAE, and HKE. The instrumental value ofEnglish is valued, but BRE, GAE and HKE are not considered to have a high status.Participants were mildly eager to learn and use English, but not to learn CME. The statusand solidarity dimensions in the VGT showed positive correlation, as did the questionnaire.The status dimension of the VGT and the questionnaire showed weak positive correlation,as did the solidarity dimension. Their implicit attitudes were affected by gender, age, grade,university, dialect area, and major. The explicit attitudes were influenced by gender,mother’s education level, and self-perceived English proficiency. The participants haveambivalent explicit attitudes towards CME in that while they give explicit positiveevaluations to CME, they refuse to learn it. Participants do not perceive Inner Circle English(BRE, GAE) as having a prominent status, which implies an awakening of Chineseuniversity students’ awareness of World Englishes or English as a Lingua Franca (ELF).